"Klapać na pyszczysku", czyli o śląskiej leksyce i frazeologii dotyczącej mówienia - Lidia Przymuszała (Ksiegarnia Akademicka Publishing, 2019)
Klapać na pyszczysku. Silesian Lexis and Phraseology Referring to Speaking The article discusses selected lexical units found in the dialects of Silesia, which refer to the act of speaking. It examines more than 190 tokens and collocations whose common denominator is the meaning of ‘speaking’. Analyzed are units referring to the content of the expression (with the main semantic component ‘to talk nonsense’), as well as those referring to physical aspects of the act of speaking, such as the clarity and accuracy of articulation (‘to speak indistinctly’, ‘to stutter’), the pace of speaking (‘to speak fast’, ‘to speak slowly’), also the tone, pitch, and intensity of the voice (‘to speak softly’, ‘to say shrilly’). An analysis of the collected material shows that these units form a semantically very heterogeneous group, and tokens and idioms which belong to it are characterized by a significant degree of semantic complexity. The article touches also the question of motivation and evaluation which is presented in the text of lexical units.